TINJAUAN YURIDIS NORMATIF EKSISTENSI ASAS LEGALITAS DALAM HUKUM PIDANA INDONESIA - Suryani Yusi; Erniwati Erniwati (Justici, 2022)
The principle of legality is one of the main principles that is used as the basis in every administration of government and state in every legal state. In criminal law, the principle of legality is related to determining whether a Criminal law can be applied to criminal acts that occur. So, if there is a crime, it will be seen whether there are legal provisions that regulate it and whether the existing rules can be applied to the crime that occurred. The criminal law system that we adhere to contains the principle of legality contained in Article 1 paragraph (1) of the Criminal Code which states that no act can be punished except for the strength of the criminal rules in the legislation that existed before the act was committed.